NGS zur Selektion innovativer Therapien – Was bringt das? - Schulmeyer, Carla; Bader, Simon; Hübner, Hanna; Rübner, Matthias; Fasching, Peter (Gynäkologe, 2021)
Next generation sequencing (NGS) describes a technology for sequencing the entire human genome, exome and transcriptome and has revolutionized genomic research. In comparison to Sanger sequencing NGS is able to sequence a whole human genome within 1 day. The results can be aligned with reference human genomes. Through DNA fragmentation, ligation of adaptors on the ends of fragments and amplification of the fragments a bioinformatics analysis is carried out, which is stored in the form of a chip and sequenced. The NGS can be used in multiple applications, especially in genetic, microbiological and oncologic research and has not yet become comprehensively established within the clinical routine. In obstetrics and gynecology, NGS is especially used in noninvasive prenatal testing (NIPT), reproductive medicine and oncology.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Breast cancer; DNA fragmentation; Genome; human; Genomics; Prenatal diagnostics